Expression of the recombinant single chain variable fragments recognizing blood antigen fused with thioredoxin in Escherichia coli - Ha, Dang Thi Ngoc; Hong, Le Thi Thu; Hai, Truong Nam (Academia Journal of Biology, 2019)
The technology of recombinant single chain variable fragments (scFvs) expression has been used in research, diagnosis and treatment of diseases. In the previous study, we studied the expression of a recombinant single chain variable fragment recognizing blood A antigen (antiA-scFv) in E. coli. However, the protein was insoluble form resulting in difficulty for purification, refolding and activity assesment. Here, we present the study on fused expression of the recombinant scFv -specific blood A antigen with thioredoxin (Trx) in the expression vector pET32a (+). The results showed that the Trx/antiA-scFv fusion protein was expressed with molecular weight of 49 kDa in a soluble form reaching 40% of the total recombinant protein. This result facilitates the optimal condition of soluble protein expression, purification and bioactivity determination of the antiA-scFv recombinant antibody.